Pengaruh Keefektifan Kepemimpinan Dan Iklim Organisasi Terhadap Kinerja Pegawai Dinas Pariwisata Di Kabupaten Tolitoli (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2016)
Correlation descriptive is used as research method in this research. Data analysisusing multiple regression. The result of this research conclude that (1) There is positive effect of leadership effectiveness and organization climate to employee performance with coefficient correlation rX1X2Y1 = 0.934 determination correlation 0.873 which showed variance 87.3 %. (2) There is positive effect of leadership effectiveness and organization climate to employee performance in prepare the planning program with coefficient correlation rX1X2Y2 = 0.913 determination correlation 0.833 which showed variance 83.3%. (3) There is positive effect of leadership effectiveness and organization climate to employee performance in doing the program process with coefficient correlation rX1X2Y3 =0.894 determination correlation 0.799 which showed variance 79.9 %. (4) There is positive effect of leadership effectiveness and organization climate to employee performance in making evaluation program with coefficient correlation rX1X2Y4 = 0.904 determination correlation 0.817 which showed variance 81.7 %.